Investigations into the fluorescence of calcitic speleothems - Beynan, Van Philip (My University, 1998)
Variations in fluorescence in calcite speleothems may record environmental changes above a cave. It is established that many display annual banding of colour or fluorescence or both, but it is not known what produces the bands or what is the environmental significance of the variability in their fluorescence or thicknesses. Analysis of speleothem feed waters at Marengo Cave, Indiana, found that peak fluorescence values are highest in the spring when soil organics are flushed into the cave or during the early Fall drought. These seasonal characteristics permit annual sequences of fluorescence intensity to be recognized in many speleothems. A comparison of seasonal variability in quantity and types of organic substances in sod and cave waters found that the former display little seasonality in organic concentrations compared to cave waters' peak yields in the spring and fall. Fluorescence studies revealed shorter peak excitation and emission wavelengths in the cave waters, due to differences in concentration and significant changes in the proportional organic assemblages. Precipitation affects the fluorescence in both waters, with the dry fall producing the highest fulvic acid and particulate organic matter yields. Molecular size fractionation determined that larger hydrophobic compounds are preferentially removed from the percolation water and the smaller hydrophilic compounds become the dominant fluorophore in cave drips. Fluorescence of twelve sample speleothems (and extracts) from a wide range of geographical environments gave similar spectra, with broad emission maxima centred around 410-430 nm and two excitation maxima at approximately 255 nm and 330 nm. Trace elements are not responsible for these spectra. Organic acids, particularly fulvic acid, were the dominant fluorophore in the calcite, confirming the Marengo Cave results that show low molecular weight (<1 kD) substances were the dominant organic fraction. Concentration of organics does not relate directly to colour hue or density in the speleothems. Annual bands were found in speleothem fluorescence/phosphorescence signals, with strong similarities between speleothems from the same cave suggesting that the signal is generated by the overlying environment. Correlations between fluorescence/phosphorescence and standard climatic variables are very tentative at present.
Keywords: Geography; Geography